2011
DOI: 10.1038/emboj.2011.203
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of positive allosteric modulation of GluN2B NMDA receptors by polyamines

Abstract: NMDA receptors (NMDARs) form glutamate-gated ion channels that have central roles in neuronal communication and plasticity throughout the brain. Dysfunctions of NMDARs are involved in several central nervous system disorders, including stroke, chronic pain and schizophrenia. One hallmark of NMDARs is that their activity can be allosterically regulated by a variety of extracellular small ligands. While much has been learned recently regarding allosteric inhibition of NMDARs, the structural determinants underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
169
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 143 publications
(177 citation statements)
references
References 64 publications
7
169
1
Order By: Relevance
“…Propping open the ATD of either the GluN1 or the GluN2 subunit increases the channel open probability (2,22). Because spermine acts as potentiator, this mechanism suggests that spermine stabilizes an open conformation of the GluN2B ATD (9). Consistent with this, the extent of spermine potentiation is much less when the GluN2B ATD is already braced open by a thiol-reactive MTS (methanethiosulfonate) reagent (9).…”
supporting
confidence: 64%
See 3 more Smart Citations
“…Propping open the ATD of either the GluN1 or the GluN2 subunit increases the channel open probability (2,22). Because spermine acts as potentiator, this mechanism suggests that spermine stabilizes an open conformation of the GluN2B ATD (9). Consistent with this, the extent of spermine potentiation is much less when the GluN2B ATD is already braced open by a thiol-reactive MTS (methanethiosulfonate) reagent (9).…”
supporting
confidence: 64%
“…ATD structure with suggested spermine-binding site and mutation sites for LRET experiments. A, crystal structure of the GluN1-GluN2B ATD dimer structure is shown highlighting the suggested spermine-binding residues in blue (PDB code 4PE5) (9,10). B, schematics of individual subunits are shown indicating the locations of mutations and the resulting amino acid sequence.…”
Section: Conformation Of the Glun2 Atd A Comparison Betweenmentioning
confidence: 99%
See 2 more Smart Citations
“…1A). Besides having essential functions in receptor assembly (10,11), recent studies of the NTDs have also revealed that the individual GluN2 (12)(13)(14) and GluN1 (15) NTDs fine-tune NMDAR gating and pharmacological properties by undergoing large-range conformational changes. The recent X-ray crystal structure of a GluN1/GluN2B NTD complex reveals a unique arrangement of the two NTD protomers with intersubunit interactions distinct from those observed in AMPA and kainate receptors (16,17).…”
mentioning
confidence: 99%